Thermogravimetric analysis (TGA) and differential scanning calometric (DSC) analysis of pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites - Siregar, Januar Parlaungan; Salit, Mohd Sapuan; Ab. Rahman, Mohd. Zaki; Mohd. Dahlan, Khairul Zaman (Universiti Putra Malaysia Press, 2011)
This paper studied the thermal behaviour of pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composite. Thermogravimetric analysis (TGA) and differential scanning calorimetric (DSC) analysis were used to measure the thermal characteristic of HIPS/PALF composites. In particular, the TGA analysis was utilized to measure the degradation and decomposition of materials in neat polystyrene, pineapple fibre, and the composites. The measurements were carried out in the temperature of 25°C â€“ 800°C, at a heating rate of 20°C min-1 and the nitrogen gas flow was 50 mL min-1. The temperature of the DSC analysis was programmed to be between 25°C â€“ 300°C. The results from TGA analysis show that the addition of pineapple fibre has improved the thermal stability of the composites as compared to neat HIPS. In addition, the effects of compatibilising agent and surface modification of PALF with alkali treated were also determined and compared.